Mémoires individuelle et collective dans l'ouvre d'Annie Ernaux et Ivan Jablonka - Gacoin-Marks, Florence (Ars et humanitas, 2018)
This paper deals with evolution of the French contemporary autobiographical novel from the personal confession to a combination of autobiographical novel, "generation" novel and social prose, which is a new trend in French literature. We will define this kind of prose - which has been developed in 20th century Slovene literature - through a reflection on certain methodological problems which are involved in "autosociobiography" (as the novelist Annie Ernaux calls it) and through the analysis of three literary works from the end of 20th century and the beginning of the 21rst: the two novels La Place (The Place, 1982) and Les Années (Years, 2008) by Annie Ernaux (born in 1940) and autobiographical narrative En Camping-car (Camper Van, 2016) by Ivan Jablonka (born in 1973).
Keywords: 20.-21. st.; 20th-21st century; autobiography; avtobiografija; collective memory; contemporary literature; Ernaux, Annie; francoska književnost; French literature; Jablonka, Ivan; književnost in sociologija; kolektivni spomin; literature and sociology; memory; sodobna književnost; spomin